Tylvalosin Tartrate Improves the Health Status of Swine Herds during Immunization with Porcine Reproductive and Respiratory Syndrome Virus-Inactivated Vaccine - Qianru Zhang; Chenchen Cui; Siyu Zhang; Xiaohong Deng; Xuehui Cai; Gang Wang (Veterinary Sciences, 2022)
Porcine reproductive and respiratory syndrome (PRRS) is a devastating disease that affects pigs and is responsible for severe economic losses. The commercial PRRSV-inactivated vaccine (CH-1a strain) in China was recently selected to control PRRS in large populations of PRRS-positive sows and was found to effectively reduce the rate of stillbirth abortion based on clinical observations. However, stress from vaccine inoculation (e.g., fever, anorexia, abortions, and slow body weight gain) usually appears after immunization on many swine farms. In this study, we fed piglets a diet medicated with tylvalosin tartrate during PRRSV-inactivated vaccine immunization. We found that tylvalosin tartrate attenuated the increase in total white blood cells induced by immunization at day one post-immunization (DPI) and induced an increase in monocyte counts after seven DPI. There was also attenuation in the intensity of the inflammatory response induced by vaccination and elevation of serum IFN-γ concentrations at three and seven DPI after immunization. The administration of tylvalosin tartrate could also attenuate the reduction in the percentage of CD8+ T cells induced by PRRSV-inactivated vaccine immunization at seven DPI. These results demonstrated that in addition to tylvalosin tartrate being able to control respiratory and enteric bacterial infections in swine farms, it can also improve the stress status of swine herds during PRRSV-inactivated vaccine immunization.